Streptococcus parasanguis Fimbria-Associated Adhesin Fap1 Is Required for Biofilm Formation - Froeliger, Eunice H. (American Society for Microbiology, 2001)
The sanguis streptococci are primary colonizers of the tooth surface and thus form the foundation for the complex multiple species biofilm known as dental plaque. In addition, these bacteria can colonize native and prosthetic heart valves and are a common cause of endocarditis. Little is known about the molecular mechanisms governing multiple or single species biofilm development within this group of organisms. Using an in vitro assay for biofilm formation, we determined that (i) Streptococcus parasanguis FW213 can form biofilms on inert surfaces such as polystyrene and (ii) environmental and nutritional factors, such as glucose, affect S. parasanguis biofilm formation. Several isogenic mutants of FW213 were tested in the biofilm assay. Strains containing mutations in fap1, a gene encoding a protein required for assembly of fimbriae, were deficient in biofilm formation. Mutants defective in recA, PepO endopeptidase activity, or the production of a fimbriae-associated protein, FimA, were still capable of biofilm formation. Phase-contrast microscopy was used to follow biofilm development by wild-type and fap1 mutant strains on plastic coverslips over time. Wild-type FW213 attached to the surface, formed aggregates of cells, and eventually formed a dense layer of cells that included microcolonies. In contrast, few fap1 mutant cells were observed attached to the surface, and no cell aggregates or microcolonies were formed. These results suggest that the long peritrichous fimbriae of FW213 are critical for the formation of biofilms on solid surfaces.